'I always have fun at work': How 'remarkable workers' employ agency and control in order to enjoy themselves. (March 2020) - Owler, Kathryn; Morrison, Rachel L.
Abstract: Organisations and associated management practices are generally considered responsible for promoting employees' enjoyment of work. Our study, on the other hand, seeks to examine the capacity of individual workers to regulate their own experience of fun. We interviewed eight 'remarkable' workers who claimed to always (or nearly always) have fun at work. We utilised a critical realist approach in the analysis that enabled the consideration of both structure and agency in the experience of workplace fun. A key research finding was that participants possessed a strong sense of control over their own happiness at work, demonstrated in four ways: (1) a priority placed on fun, (2) a sense of responsibility for fun, (3) a positive orientation to the world and (4) a sense of mastery and challenge in work tasks. Research findings may inspire both individual workers and organisations to adopt an agentic outlook in the workplace, implementing strategies that enhance employee control.